2021
DOI: 10.3390/coatings11060702
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pulsed RF GD-OES and HAXPES for Quantified Depth Profiling through Coatings

Abstract: Chemical characterization at buried interfaces is a real challenge, as the physico-chemical processes operating at the interface govern the properties of many systems and devices. We have developed a methodology based on the combined use of pulsed RF GD-OES (pulsed Radio Frequency Glow Discharge Optical Emission Spectrometry) and XPS (X-ray Photoelectron Spectroscopy) to facilitate the access to deeply buried locations (taking advantage of the high profiling rate of the GD-OES) and perform an accurate chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…XPS showed reduction of the C and O content by >90% without Ar implantation (evidenced by a lack of signal from Ar 2p); HAXPES then showed no signal from O or C. It is known that HAXPES is not sensitive to an ion-induced damage layer at the surface. 8…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…XPS showed reduction of the C and O content by >90% without Ar implantation (evidenced by a lack of signal from Ar 2p); HAXPES then showed no signal from O or C. It is known that HAXPES is not sensitive to an ion-induced damage layer at the surface. 8…”
Section: Resultsmentioning
confidence: 99%
“…7 We have also combined HAXPES with other destructive depth-profiling techniques, where it was found that HAXPES is able to sample below the damage layer created by plasma etching in glow discharge optical emission spectroscopy (GDOES), a technique which has traditionally been challenging to calibrate. 8 This demonstrates that HAXPES is sensitive to the material below the altered layer on an ion-etched surface, and therefore offers measurement of the unmodified chemical composition prior to ion-induced damage and preferential sputtering. As all forms of etching (using monoatomic and more recent cluster sources) potentially alter material systems, 9 an important benefit of HAXPES analysis is to provide a minimally-destructive measurement of the material below the topmost surface.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…HAXPES (hard X-ray photoelectron spectroscopy) would bring additional information about deeper changes in the composition and an assessment of the damaged overlayer thickness, 40 but it is limited by the stability of the perovskite layer under high-energy X-ray radiation. The approach proposed here, with the complementary use of XPS and PL, aims at yielding a reliable diagnosis of the surface modifications of the irradiated perovskite as well as an evaluation of the indepth perturbation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 23 ] One can also mention that it has been proposed to couple GD‐OES and XPS to combine fast sputtering process and chemical information. [ 24,25 ] However, these techniques are difficult to implement for perovskite photovoltaic layers investigation with a reasonable acquisition time, with the keeping of the analysis chamber as clean as possible to preserve UHV conditions and with the avoiding of redeposition concerns, of iodide especially. [ 26 ] Moreover, the sample size is a concrete problem when samples are outgazing.…”
Section: The Gd‐oes Technique: Advantages and Limitationsmentioning
confidence: 99%